Características nutritivas de la saccharina rústica con diferentes niveles de urea - Herrera Herrera, Rocío del Carmen (2014)
Sugar cane is a grass with a high energy content having nutritional limitations due to its low percentage of protein, so it is necessary to supplement with a protein source for rapid degradation through the development of rustic saccharina, which represents an alternative ruminant feeding in achieving improve their nutritional profile. The aim of this study was to evaluate changes in chemical composition and digestibility in situ de saccharina rustic effect of adding urea levels. Three fistulated crossbred Brahman cattle were used to determine the digestibilidad in situ using nylon bags, with a design of randomized complete block with three treatments, three replicates six incubation times (3, 6, 12, 24, 48, 72 h ) animals of each treatment received saccharina made with 1, 1.5 and 2% urea plus salts minerals, determining in each treatment, chemical composition and in situ digestibility of: dry matter (DISMS), organic matter (DISMO), fiber neutral detergent (DISFDN), acid detergent fiber (DISFDA) and protein (DISP). The results of the chemical composition showed a progressive increase in the percentage of nutritional components saccharina with each level of urea, which shows that it was improved nutritional value, while results of in situ digestibility yielded significant estadísticano difference between and h incubation treatments except (DISP) which positively affected when it contained the highest level of urea (2%).